Effectiveness of Ayurvedic and Panchakarma Therapies in Managing Chronic Kidney Disease: A Case Study Report (Advances in Applied Biological Research, 2025)
Chronic kidney disease (CKD) is defined as a progressive disease that affects the  overall health of kidney. CKD is diagnosed in five stages based on its symptoms and  the structure and function of kidney. CKD can be significantly influenced by several  lifestyle factors. Poor dietary habits, such as high intake of salt, sugar, unhealthy  fats, and processed foods, contribute to obesity, hypertension, and diabetes, key  risk factors for CKD. Hence, the CKD treatment requires a multifaceted approach  including adopting a healthy lifestyle with a balanced diet, regular exercise, stress  management, and proper hydration. This case report focuses on a 31-year-old  female patient with CKD for 2 years and hypertension for 6 months who received  Ayurvedic treatment at Jeena Sikho Lifecare Limited Hospital, Derabassi. The  treatment method administered on her was a combination of customized Ayurveda and Panchakarma therapies, resulting in significant progresses in her symptoms,  kidney health and function, and general life quality. After 7 days of IPD, the  patient showed improvement in Blood Urea and Serum Creatinine, also reported  relief from periorbital swelling and other symptoms. This study highlights the  potential of Ayurveda as an economical alternative to conventional treatments,  especially for individuals with limited financial resources who face challenges in  accessing advanced healthcare. While the results are encouraging, further research  with larger randomized controlled trials is essential to assess the effectiveness and  safety of Ayurvedic treatments for CKD.
Keywords: Chronic Kidney Disease (CKD); Glomerular Filtration Rate; Ayurveda; Panchakarma; Hypertension; Vrikka Vikar